Tomato Cultivars Resistant or Susceptible to Spider Mites Differ in Their Biosynthesis and Metabolic Profile of the Monoterpenoid Pathway - Weinblum, Nati; Cna'ani, Alon; Yaakov, Beery; Sadeh, Adi; Avraham, Lior; Opatovsky, Itai; Tzin, Vered (Frontiers in Plant Science, 2021)
The two-spotted spider mite (TSSM; Tetranychus urticae) is a ubiquitous polyphagous arthropod pest that has a major economic impact on the tomato (Solanum lycopersicum) industry. Tomato plants have evolved broad defense mechanisms regulated by the expression of defense genes, phytohormones, and secondary metabolites present constitutively and/or induced upon infestation. Although tomato defense mechanisms have been studied for more than three decades, only a few studies have compared the natural mite resistance between domesticated cultivars at the molecular level. The main goal of our research was to reveal the molecular differences between two tomato cultivars with similar physical (trichome morphology and density) and agronomic traits (fruit size, shape, color, cluster architecture), but with contrasting TSSM susceptibility. A net house experiment indicated a mite-resistant difference between the cultivars, and a climate-controlled performance and oviposition bioassay supported these findings. A transcriptome analysis of the two cultivars after three days of TSSM infestation revealed changes in genes associated with primary and secondary metabolism, including salicylic acid and volatile biosynthesis (volatile benzenoid ester and monoterpenes). The Terpene synthase genes TPS5, TPS7, and TPS19/20, encoding enzymes that synthesize the monoterpenes linalool, β-myrcene, limonene, and β-phellandrene were highly expressed in the resistant cultivar. The volatile profile of these cultivars upon mite infestation for 1, 3, 5, and 7 days revealed substantial differences in monoterpenoid and phenylpropanoid volatiles, results consistent with the transcriptomic data. Comparing the metabolic changes that occur in each cultivar and upon mite-infestation indicated that monoterpenes are the main metabolites that differ between cultivars (constitutive levels), while only minor changes occur upon TSSM attack. To test the effect of these volatile variations on mites, we subjected both the TSSM and its corresponding predator, Phytoseiulus persimilis, to an olfactory choice bioassay. The predator mites were only significantly attracted to the TSSM pre-infested resistant cultivar and not to the susceptible cultivar, while the TSSM itself showed no preference. Overall, our findings revealed the contribution of constitutive and inducible levels of volatiles on mite performance. This study highlights monoterpenoids’ function in plant resistance to pests and might inform the development of new resistant tomato cultivars.